Study of whistler mode instability in Saturn's magnetosphere - Singhal, R.P.; Tripathi, A.K. (Copernicus GmbH, 2006)
A dispersion relation for parallel propagating whistler mode waves has been applied to the magnetosphere of Saturn and comparisons have been made with the observations made by Voyager and Cassini. The effect of hot (suprathermal) electron-density, temperature, temperature anisotropy, and the spectral index parameter, κ, on the temporal growth rate of the whistler mode emission is studied. A good agreement is found with observations. Electron pitch angle and energy diffusion coefficients have been obtained using the calculated temporal growth rates.
Keywords: anisotropy; dispersion; electron density; growth rate; instability; magnetosphere; Saturn; spectrum; temperature